Analogy of Machine Learning Approaches and BERT for Sentiment Analysis (Journal of Information Technology and Digital World, 2022)
For assessing customer sentiment in Amazon product reviews, this article compares two machine learning algorithms and a deep learning method, BERT (Bidirectional Encoder Representations from Transformer). Machine learning is the most practical approach in the current era of artificial intelligence for training a neural network to handle the majority of real-world issues. In this paper, the real-world scenario of sentiment analysis is considered, ideally the classification problem. Firstly, the data is provided into a model, which evaluates the feature that uses the Term Frequency (TF) and Inverse Document Frequency (IDF) pre-processing methods. Secondly, the algorithms, Naive Bayes classifier and Support Vector Machine are used to analyze the sentiment of the consumer comments and compute metrics like F1 score. Finally, the input data is fed for BERT to process and compute the F1 score. To summarize, this study is to provide a detailed comparative analysis of machine learning techniques and deep learning algorithms.
Keywords: Sentiment analysis; Naïve Bayes classifier; SVM; BERT